What we owe to each other - Scanlon, Thomas (Belknap Press of Harvard University Press, 2000)
How do we judge whether an action is morally right or wrong? And if it is wrong, what reason does that give us not to do it? In this reconsideration of moral reasoning, T.M. Scanlon offers new answers to these enduring questions. According to his contractualist view, thinking about right and wrong involves considering what we do in terms that could be justified to others and that they could not reasonably reject. Scanlon shows how familiar moral ideas such as fairness and responsibility can be understood through their role in this process of mutual justification. He argues that desires do not provide us with reasons, and that well-being is not as important for rational decision-making as it is commonly held to be. Scanlon believes that contracutalism allows for most of the variability in moral requirements that relativists have claimed, while still accounting for the full force of our judgments of right and wrong.